Vander's human physiology - Widmaier, Eric P.; Raff, Hershel, 1953-; Strang, Kevin T.; Vander, Arthur J., 1933- (New York, NY : McGraw Hill LLC, 2023)
"We are pleased to offer an integrated package of textual and digital material to help deliver basic and clinical content, real-life applications, and educational technologies to students of physiology. With the 15th edition of Vander's Human Physiology, all these pieces come together to facilitate learning and enthusiasm for understanding the mechanisms of body function. The cover of this edition reflects the book's focus on homeostasis, one of the key "General Principles of Physiology" elaborated upon in Chapter 1 and reinforced throughout. In addition, the cover illustrates the book's emphasis on processes at all levels of system, organ, tissue, and cellular function. As in previous editions, these themes are always related to pathophysiology through the use of compelling clinical case studies in all chapters, and a final chapter with several cases that integrate material across the entire book. An exciting development with this edition is the addition to the author team of Todd Shoepe from Loyola Marymount University. In addition to his background in exercise physiology, Professor Shoepe is an expert in cutting-edge learning technologies and has assumed the role of digital author beginning with this edition. The big winners in this context will be students using the book, who will benefit from the combined expertise of Professor Shoepe and the skilled editorial team that created the extremely successful Connect digital content for McGraw-Hill Education. We are certain that you will find the 15th edition of this textbook to be the most up-to-date and comprehensive book available for students of physiology. Thank you and happy reading!"-
Includes bibliographical references and index.
Keywords: Human physiology